Revisiting the Neighborhood: How L2 Proficiency and Neighborhood Manipulation Affect Bilingual Processing - Mulder, Kimberley; van Heuven, Walter J. B.; Dijkstra, Ton (Frontiers in Psychology, 2018)
We conducted three neighborhood experiments with Dutch-English bilinguals to test effects of L2 proficiency and neighborhood characteristics within and between languages. In the past 20 years, the English (L2) proficiency of this population has considerably increased. To consider the impact of this development on neighborhood effects, we conducted a strict replication of the English lexical decision task by van Heuven, Dijkstra, & Grainger (1998, Exp. 4). In line with our prediction, English characteristics (neighborhood size, word and bigram frequency) dominated the word and nonword responses, while the nonwords also revealed an interaction of English and Dutch neighborhood size. The prominence of English was tested again in two experiments introducing a stronger neighborhood manipulation. In English lexical decision and progressive demasking, English items with no orthographic neighbors at all were contrasted with items having neighbors in English or Dutch (‘hermits’) only, or in both languages. In both tasks, target processing was affected strongly by the presence of English neighbors, but only weakly by Dutch neighbors. Effects are interpreted in terms of two underlying processing mechanisms: language-specific global lexical activation and lexical competition.